Study on the effect of gasification agents on the integrated system of biomass gasification combined cycle and oxy-fuel combustion. (1st September 2020) - Xiang, Yanlei; Cai, Lei; Guan, Yanwen; Liu, Wenbin; Cheng, Zeyang; Liu, Zexi
Abstract: An integrated system of biomass gasification combined cycle with oxy-fuel combustion was proposed. Considering the neutral character of biomass, the "negative emissions" were achieved. Different gasifying agents, including steam, CO2, steam + O2, CO2 + O2, steam + CO2, and steam + CO2 + O2 were examined. The steam and CO2 in gasifying agents were directly separated from flue gas in power generation unit. The effects of equivalence ratios and gasifying agent to biomass ratios on syngas production were studied. The results revealed that steam contributed to the yield of H2, while it inhibited the generation of CO. CO2 in the gasifying agent promoted the yield of CO. O2 had little impact on H2 production, but it significantly reduced the generation of CO and CH4 . The introduction of O2 in gasifying agent reduced the syngas LHV while it generally raised the gasification efficiency. Furthermore, when O2 was used to realize the autothermal gasification process, the net power generation efficiencies under steam + O2 gasification, CO2 + O2 gasification and steam + CO2 + O2 gasification were 26.3%, 28.3% and 27.6%, respectively. These efficiencies were competitive considering the biomass disposal and carbon capture. Highlights: ►The biomass gasification combined cycle and oxy-fuel combustion are integrated. ►The effects of gasifying agent on syngas composition and power generation are studied. ►The steam and CO2 in the gasifying agent are obtained from flue gas. ►The power generation efficiency ranges from 26.3% to 28.3% with negative emissions.